1996
DOI: 10.1007/bf02173982
|View full text |Cite
|
Sign up to set email alerts
|

A vital function for mitochondrial DNA in the petite-negative yeastKluyveromyces lactis

Abstract: Petite-negative yeasts do not form viable respiratory-deficient mutants on treatment with DNA-targeting drugs that readily eliminate the mitochondrial DNA (mtDNA) from petite-positive yeasts. However, in the petite-negative yeast Kluyveromyces lactis, specific mutations in the nuclear genes MG12 and MG15 encoding the alpha- and gamma-subunits of the mitochondrial F1-ATPase, allow mtDNA to be lost. In this study we show that wild-type K. lactis does not survive in the absence of its mitochondrial genome and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This is in contrast to S. cerevisiae , which is petite positive as deletions in the mitochondrial DNA are not lethal. Mutations in K. lactis were identified that convert the cells from petite negative to petite positive and the complementation group was named m itochondrial g enome i ntegrity ( mgi ) 113 114 115 116 117 118 . Surprisingly, the mgi mutations mapped in the genes encoding α-, β-, and γ-subunits of the mitochondrial ATP synthase.…”
Section: Structure and Organization Of The F 1 F mentioning
confidence: 99%
“…This is in contrast to S. cerevisiae , which is petite positive as deletions in the mitochondrial DNA are not lethal. Mutations in K. lactis were identified that convert the cells from petite negative to petite positive and the complementation group was named m itochondrial g enome i ntegrity ( mgi ) 113 114 115 116 117 118 . Surprisingly, the mgi mutations mapped in the genes encoding α-, β-, and γ-subunits of the mitochondrial ATP synthase.…”
Section: Structure and Organization Of The F 1 F mentioning
confidence: 99%
“…lactis and S . pombe MGM101 homologues have been identified ( Chen et al, 1993 ; Clark-Walker and Chen, 1996 ; see Fig. 1 ).…”
mentioning
confidence: 99%
“…In addition to the loss of or mutations in mtDNA (i.e., cytoplasmic petite), mutations occurring in the nuclear genome can also generate the petite phenotype (i.e., nuclear petite) if the nuclear genes required for respiratory growth or encoding mitochondrial proteins are disrupted. Moreover, mtDNA loss is lethal in the wildtype yeast species Kluyveromyces lactis (petite-negative) [ 10 ]. Thus, the petite phenotype reflects stresses that cells have to deal with when respiratory dysfunction occurs.…”
Section: Introductionmentioning
confidence: 99%